2011
DOI: 10.1111/j.1365-2753.2011.01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and enablers of evidence‐based practice in perinatal care in the SEA‐ORCHID project

Abstract: Effective interventions to align practice with evidence rely on identifying and addressing barriers to practice change. The barriers identified in this study may be useful for those designing similar clinical practice improvement projects, as well as for continued efforts to improve practice in the SEA-ORCHID hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…These data indicate that the programme is highly practical in terms of its organization, teaching staff and methodology. These data are interesting given the importance that these quality indicators are acquiring as a result of studies on the dynamics of human processes in general, and educational processes in particular, which show that relationships between the participants involved give rise to a particular internal climate which, on many occasions, leads to emotionally close relationships and positive stimuli that are much more valuable than the simple results of the learning process [43–46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that the programme is highly practical in terms of its organization, teaching staff and methodology. These data are interesting given the importance that these quality indicators are acquiring as a result of studies on the dynamics of human processes in general, and educational processes in particular, which show that relationships between the participants involved give rise to a particular internal climate which, on many occasions, leads to emotionally close relationships and positive stimuli that are much more valuable than the simple results of the learning process [43–46].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that the programme is highly practical in terms of its organization, teaching staff and methodology. These data are interesting given the importance that these quality indicators are acquiring as a result of studies on the dynamics of human processes in general, and educational processes in particular, which show that relationships between the participants involved give rise to a particular internal climate which, on many occasions, leads to emotionally close relationships and positive stimuli that are much more valuable than the simple results of the learning process [43][44][45][46]. The efficiency indicators show a drop in the consumption of toxic substances, an improvement in health habits, a significant increase in the perception of knowledge and high satisfaction levels, as well as specifications of the improvements called for by the population that will allow specific strategies to be designed to increase quality.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of evidence-based perinatal care can be effective (23), prenatal education has not been well researched in the studies. Also, contrary to the advice of existing evidence, education does not have woman-centered focus, thus behavior changes do not seem to be fit.…”
Section: Discussionmentioning
confidence: 99%
“…on whether or not to implement guidelines. This barrier has been pointed out in several studies carried out in various settings [9][10][11][12][13][14][15][16][17][18][19][20][21][22] . Moreover, Chapman et al has observed that if a team practice is tailored according to the team head, the choice of which CPG to adopt might change if a new team head is appointed [19] .…”
Section: Table 1: Demographics Of Participantsmentioning
confidence: 99%
“…It can be argued that the physicians in this study perceived their lack of awareness of the guideline and a lack of knowledge as a barrier to implementation. This has been one of the most reported barriers across studies in this topic [20][21][22]24] . This lack of knowledge could be divided into two types; first, the lack of knowledge about the guideline itself which has been labeled as awareness in some studies [23,25] , and second, lack of knowledge in the usage or application of the guidelines, which has been labeled as skills in other studies [22,24] .…”
Section: Table 1: Demographics Of Participantsmentioning
confidence: 99%